NILAI-NILAI TOLERANSI ISLAM DI NEGARA KEBANGSAAN INDONESIA DALAM PERSPEKTIF AKSIOLOGI - Jirzanah, Jirzanah (Jurnal Filsafat "WISDOM", 2013)
Islamic values are expected to be a barrier to excessive nationalistic. Analysis on Islamic values and tolerance from the point of view of axiology is important, because Islam is not just giving nature a noble and religious attitudes, but also respect for moral rules and actions. Axiological analysis is done by placing the basic Islamic values, moral norms and principles of the nation state in an universal hierarchy values. The purpose of this article is to formulate a reflective relevance of Islamic values and tolerance for the development of the nation state. The basic values of Islamic law according to the Quran is a religious and humanity values particularly noble mind. The law of God is a source of values to humanity values and the state of moral principles. Humanity values especially nobility mind formed the basic of freedom of thought and will. Nobility mind basic to foster unity, cooperation, freedom, democracy, and justice. Islamic teachings of tolerance are very relevant to the Indonesian nation state principle. Islam teaches religious nature and noble attitude, the attitude of respect for moral rules and actions. Tolerant teachings of Islam comes from religious values and universal humanities, so do not know the theory, attitudes, and practices that are based on violence and coercion in the field of divinity, politics, and economics.